Race tactics in the heats of a sprint cross-country skiing competition - Haugnes, P.; Kocbach, J.; Talsnes, R.; Noordhof, D.; Ettema, G.; Sandbakk, Ø. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Aim The purpose of this study was to examine the influence of race tactics on performance in the heats of an international sprint cross-country (XC) skiing competition in the classical style.